2015
DOI: 10.1016/j.eurpolymj.2015.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Electrosprayed poly(butylene succinate) microspheres loaded with indole derivatives: A system with anticancer activity

Abstract: Electrospraying of poly(butylene succinate) and its mixture with different indole derivatives was successfully performed using chloroform as solvent and relatively low flow rates and concentrations. Morphology of particles (size, diameter distribution and surface texture) and encapsulation efficiency were dependent on the loaded drug and specifically on the type of substituent (methyl or phenyl) and its position in the indole core. In general, particles showed a raisin-like morphology caused by the shell colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The most recent work, published by Murase et al in 2015, explores the usefulness of the electrospray technique for preparing PBS microspheres to encapsulated indoles. They found a strong correlation of i) the microparticles structure with the processing variables; ii) the encapsulation efficiency with the chemical structure of the encapsulated substance; and iii) the release profiles with the composition of the receiving fluid …”
Section: Introductionmentioning
confidence: 98%
“…The most recent work, published by Murase et al in 2015, explores the usefulness of the electrospray technique for preparing PBS microspheres to encapsulated indoles. They found a strong correlation of i) the microparticles structure with the processing variables; ii) the encapsulation efficiency with the chemical structure of the encapsulated substance; and iii) the release profiles with the composition of the receiving fluid …”
Section: Introductionmentioning
confidence: 98%
“…No positively charged group or polymer has been used to modify PBS. As for the applications of PBS‐based copolymers as drug carriers, there are some studies reported of microcapsules, microspheres, scaffolds or films of PBS as drug carriers . Few studies of micelles with PBS as the hydrophobic core have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these two monomers are accessible from renewable resources; therefore it is considered as a promising polymer for development. To our knowledge, some work has been reported about microcapsules, microspheres, scaffolds or films of PBS as drug carriers . However, few studies of micelles with PBS as the hydrophobic core have been reported.…”
Section: Introductionmentioning
confidence: 99%